Irshād : Dar maʿrifat u waʿẓ u akhlāq - Qalānisī, Abū Muḥammad ʿAbdallāh (Miras Maktoob, ISBN: 9789004365452., 2019)
According to Majid Fakhry, ethical theories in Islam may be divided into four categories: 1. scriptural morality (moral precepts and judgments from the Qurʾān and the Traditions); 2. theological theories (rationalist interpretations of scriptural morality based on philosophical or theological methods and categories developed in the eighth and ninth centuries); 3. philosophical theories (ultimately relying on Greek sources, mainly Plato and Aristotle in neo-Platonic interpretations); 4. religious theories (based on the Qurʾānic view of man and his position in the universe, and differing from theological theories in that they were not dialectical, not polemical, and more concerned with moral theory than with questions of methodology). The present work comes under the last category, to which it adds an element of mysticism. Besides the more general sources and authorities, it also refers to scholars and mystics from Transoxania specifically, the work having been written there in the early 6th/12th century. Contains word material from that region.